Diseño de un sistema de Responsabilidad Empresarial bajo las Normas ISO 26000, para el crecimiento empresarial en la Comercializadora de Insumos y Productos Agropecuarios “CIPROAGRO” en la ciudad de Latacunga - Caiza Mullo, Milton Marcelo (2022)
This research project was carried out in Cotopaxi province, Latacunga canton, within the company "CIPROAGRO", with the aim to design a guide focused on corporate social responsibility, based on the ISO 26000 standard, the importance RSE and the benefits that it brings for workers and society in general. RSE is addessed at all institutions that wish to achieve comprehensive and sustainable development over time, through different strategies that allow these organizations to assume a leading role in the society progress. The scientific theoretical consideration understanding, initiatives, credibility, organizational practices, communication and the characteristics Social Corporate Responsibility, it will help the study support the most well-known standard in quality management such as ISO 26000. The methodology of the investigation is descriptive nature due to the need to implement this type of norms in the company, it is also in the field because it was worked directly in the company "CIPROAGRO".